MangoBase: a genomics portal and gene expression atlas for Mangifera indica - Gómez-Ollé, Aynhoa; Bullones, Amanda; Hormaza Urroz, José Ignacio; Mueller, Lukas A.; Fernández-Pozo, Noé (MDPI, 2023)
Mango (Mangifera indica L.) (2n = 40) is a member of the Anacardiaceae family, which was domesticated at least 4000 years ago in Asia. Mangoes are delicious fruits with great nutritional value. They are one of the major fruit crops worldwide, cultivated in more than 100 countries, with a production of more than 40 million tons. Recently the genome sequences of several mango varieties have been released, but there are no bioinformatics platforms dedicated to mango genomics and breeding to host mango omics data. Here, we present MangoBase, a web portal dedicated to mango genomics, which provides multiple interactive bioinformatics tools, sequences, and annotations to analyze, visualize, and download omics data related to mango. Additionally, MangoBase includes a gene expression atlas with 12 datasets and 80 experiments representing some of the most significant mango RNA-seq experiments published to this date. These experiments study mango fruit ripening in several cultivars with different pulp firmness and sweetness or peel coloration, and other experiments also study hot water postharvest treatment, infection with C. gloeosporioides, and the main mango tree organ tissues
Keywords: Mangos - Genética - Proceso de datos; Genómica - Proceso de datos; Mango; Mangifera indica; Bioinformatics; Genomics; Gene expression; RNA-seq; Database; Bioinformatics tools; Fruit ripening